Efficient and organic host–guest room-temperature phosphorescence: tunable triplet–singlet crossing and theoretical calculations for molecular packing. Issue 19 (13th April 2021) - Lei, Yunxiang; Yang, Junfang; Dai, Wenbo; Lan, Yisha; Yang, Jianhui; Zheng, Xiaoyan; Shi, Jianbing; Tong, Bin; Cai, Zhengxu; Dong, Yuping
Abstract : Molecular dynamics simulations were used to simulate the molecular conformation and interaction between hosts and guests. This work provides a new concept for the study of molecular packing for the investigation of the luminescence mechanism. Abstract : Organic host–guest doped materials exhibiting the room temperature phosphorescence (RTP) phenomenon have attracted considerable attention. However, it is still challenging to investigate their corresponding luminescence mechanism, because for host–guest systems, it is very difficult to obtain single crystals compared to single-component or co-crystal component materials. Herein, we developed a series of organic doped materials with triphenylamine (TPA) as the host and TPA derivatives with different electron-donating groups as guests. The doped materials showed strong fluorescence, thermally activated delayed fluorescence ( τ : 39–47 ms), and efficient room temperature phosphorescence ( Φ phos : 7.3–9.1%; τ : 170–262 ms). The intensity ratio between the delayed fluorescence and phosphorescence was tuned by the guest species and concentration. Molecular dynamics simulations were used to simulate the molecular conformation of guest molecules in the host matrix and the interaction between the host and guest molecules. Therefore, the photophysical properties were calculated using the QM/MM model. This work provides a new concept for the study of molecular packing of guest molecules in the host matrix.